Demographic development of the countries of Northern Europe: current trends for the Ukrainian experience - Hudzelyak, Iryna (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Problem statement. The current demographic parameters of Northern Europe are due to the absence of large human losses in the two world wars, and domestic political and socio-economic stability in the countries. As a result, a model of the demographic behavior of the population was formed, which for a long time ensured natural and migration growth. Therefore, the demographic parameters of the region can be considered a benchmark for developing measures to overcome demographic threats in the post-war period in Ukraine.The purpose of the study is a spatial analysis of the demographic development of the countries of Northern Europe - Norway, Sweden, Finland, Denmark and Iceland.Methods. The study was carried out on the basis of official data of the Nordic Council and Eurostat. Using the statistical method, the dynamics of the population, the main indicators of demographic processes and structures, migration and ethno-structural changes were assessed.Results. Effective demographic policy in the countries of Northern Europe had a short-term effect. In all countries, the birth rate has significantly decreased, which no longer ensures the simple reproduction of generations. The transition to narrowed reproduction has become irreversible. Population growth rates have decreased significantly. Population growth in all countries is mainly provided by migration growth. Thanks to immigration and high birth rates compared to other European countries, the region has managed to fully use the demographic dividend that has ensured economic growth. However, the influx of migrants has not solved the problem of declining birth rates, as migrants quickly adopt the norms of low-childbearing reproductive behavior of host societies. The increase in the level of demographic aging and the decrease in the coefficient of potential support for the elderly have put the countries of the region in need of introducing new and non-standard measures in various spheres of society. The implementation of such a policy in the future may become a reference example for post-war Ukraine. Demospatial disparities are increasing in the region at the subnational level: many rural areas are depopulating, and urban regions, especially metropolitan agglomerations, are growing. The worst demographic situation has developed in Finland in the border areas with Russia, where the rates of depopulation are the highest in the region. A powerful influx of migrants from Asia and Africa has contributed to the ethnic and religious diversification of society. In recent years, the share of Ukrainians has been growing. In Northern Europe, the ethnolinguistic dominance of indigenous peoples has noticeably weakened. Other internal problems associated with the weak integration of migrants into host societies have become more acute, and tension is emerging in society. The experience of the countries of Northern Europe is valuable for understanding the scenarios of demographic development of Ukraine, the development of demographic and migration policies, and the strategy of post-war adaptation of the economy, social system, and political sphere to new demographic realities.